50% dextrose versus normal saline as distension media during cystoscopy for assessment of ureteric patency. (April 2016) - Narasimhulu, Deepa Maheswari; Prabakar, Cheruba; Tang, Nancy; Bral, Pedram
Abstract: Objective: To compare the visualization of ureteric jets when using 50% dextrose (D 50) as opposed to normal saline (NS) as distension media during cystoscopy. Study design: Cross sectional study. Methods: Two patients each had two cystoscopy videos recorded at the time of a ureteric jet; one using NS and the other using D50 resulting in two sets of paired videos (four videos). A fifth cystoscopy video was recorded, as a control, at a time when there was no ureteric-jet. Fifty participants including attending physicians, residents and medical students were recruited at an academic-affiliated community hospital. Participants were blinded to the medium used and viewed each of the five videos. Participants assessed each video for presence of a ureteric-jet, ease of interpretation, and compared the paired D50 and NS videos for clarity of ureteric-jets. Main outcome measures: Participant's assessment of clarity of the ureteric jets when D50 was used as compared to when NS was used in the paired videos. Results: All 100 observations of the two D50 videos with jets identified the presence of a jet; for the NS videos, 96/100 observations identified a jet, 2/100 did not identify a jet and 2/100 were unsure. 48/50 observations of the video with no jet were correct, while 2/50 were unsure. Participants rated the ureteric-jets to be clearer in videos with D50 (86% vs 14%, P < 0.001); and had difficulty interpreting cystoscopy videos with NS (62% vs 2%, OR: 80, 95% CI: 10.2–627.6). Conclusion: Participants preferred the clarity of the ureteric-jet when 50% dextrose was used as the distension medium during cystoscopy as compared to normal saline.